Volatilitas Saham Sektor Teknologi yang Terdaftar di Indeks Saham Syariah Indonesia pada Masa Pandemi COVID-19 - Widya Sari; Susilo Setiyawan (Jurnal Accounting Information System (AIMS), 2023)
Based on the results of data documentation, that the background to this research is investment risk, especially during the COVID-19 pandemic and also the uncertainty of stock returns. This study aims to analyze which technology companies have the highest and lowest volatility during the COVID-19 pandemic and find out which univariate ARCH-GARCH model is the best. This research is a descriptive quantitative research, in which the company sample selection uses a purposive sampling method. With the criteria of stocks belonging to the technology sector on the Indonesia Stock Exchange, and also having to be included in the List of Sharia Securities consecutively, to fulfill the research period. The data analysis used in this study is descriptive statistical analysis and time series analysis with 10 samples of technology company stock data. The results showed that the technology company with the highest volatility was PT NFC Indonesia Tbk. (NFCX). Meanwhile, the technology company with the lowest volatility is PT Hensel Davest Indonesia Tbk. (HDIT). The model that best describes the volatility of technology companies during the COVID-19 pandemic is ARCH (2.2).